#TITLE_ALTERNATIVE# - ZAKARIA , MUHAMMAD
This nal project will discuss the problems of decision making that was found during the author followed an internship program at the social foundation. One of the activities carried out by the Foundation is classroom reno- vation in four dierent areas in a regional. In implementation, the Foundation still has problems in the process of determining the classroom that will be renovated so the renovation that was done still out of target and the usage of the allocated funds is still not optimal. In this nal project is conducted to create a mathema- tical method to select classrooms which will be renovated so the renovation can reach the target and the allocated fund is optimally distributed. This problem is identied as multiple choice knapsack problem with the addition of some con- straints. In the process of selecting the classroom, the Foundation considers the need of renovation (utilities), equitable renovations at schools in each region and the submission of the allocated funds the amount of funds needed to renovate a classroom in a school. In the completion of this problem, the author uses the Greedy algorithm by considering factor of the selection as the eciency factor which is dene as utility divided by necessary funds.